Spatial distribution of mortality by homicide and social inequalities according to race/skin color in an intra-urban Brazilian space Distribuição espacial da mortalidade por homicídio e desigualdades sociais segundo a raça/cor em um espaço intra-urbano no Brasil - Edna Maria de Araújo; Maria da Conceição Nascimento Costa; Nelson Fernandes de Oliveira; Francisco dos Santos Santana; Maurício Lima Barreto; Vijaya Hogan; Tânia Maria de Araújo (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2010)
INTRODUCTION: In Brazil, deaths by external causes rank first in the mortality statistics. Nevertheless, studies which investigate the relationship between mortality by external causes and race/skin color are scarce. OBJECTIVES: To evaluate the relative contribution of race/skin color to the spatial distribution of mortality by homicide in Salvador, state of Bahia, Brazil, in the period 1998 - 2003. MATERIAL AND METHODS: This is a spatial aggregate study including secondary data on 5,250 subjects, using a unit of analysis called the "weighting area" (WA). Annual average death rates by homicide were estimated. The Global and Local Moran Index were used to evaluate the presence of spatial autocorrelation and the Conditional Auto Regressive (CAR) model was employed to evaluate the referred effect, using the R statistical package. RESULTS: Global and Local Moran's I tests were significant. CAR regression showed that the predicted mortality rate increases when there is a growth in the proportion of black males aged between 15 and 49 years. Geometrically weighted regression (GWR) showed a very small variation of the local coefficients for all predictors. CONCLUSION: We demonstrated that the interrelation between race, violence and space is a phenomenon which results from a long process of social inequality. Understanding these interactions requires interdisciplinary efforts that contribute to advancement of knowledge that leads to more specific Public Health interventions. INTRODUÇÃO: No Brasil, as mortes por causas externas vêm ocupando as primeiras posições nas estatísticas de mortalidade. No entanto, são escassos os estudos que investigam a relação entre mortalidade por causas externas e raça/cor da pele. OBJETIVOS: Avaliar a contribuição relativa da raça/cor da pele na distribuição espacial da mortalidade por homicídio em Salvador, BA, Brasil no período de 1998 a 2003. MATERIAL E METODOS: Estudo de agregado espacial cuja unidade de análise é "área de ponderação" (AP) e que teve a inclusão de 5.250 sujeitos. Foram utilizados dados secundários e taxas médias anuais estimadas de mortes por homicídio. Utilizou-se o Índice Global e Local de Moran para avaliar a presença de autocorrelação espacial e o modelo "Conditional AutoRegressive" (CAR) para avaliar o referido efeito, utilizando-se o pacote estatístico R. RESULTADOS: Os testes I de Moran global e local foram significantes. A regressão CAR mostrou que a taxa predita de mortalidade por homicídio aumenta quando há um aumento na proporção de população masculina negra de 15 a 49 anos de idade. Regressão geograficamente ponderada (GWR) mostrou uma pequena variação dos coeficientes locais para todos os preditores. CONCLUSÃO: A interrelação entre raça, violência e espaço faz parte de um longo processo de desigualdade. Portanto, o seu entendimento requer a junção de esforços interdisciplinares que contribuam para ampliar o conhecimento sobre o tema e conseqüentemente orientar intervenções de Saúde Pública mais especificas.